2013
DOI: 10.1353/rhe.2013.0043
|View full text |Cite
|
Sign up to set email alerts
|

Documenting Attitudes toward Undocumented Immigrant Access to Public Education: A Multilevel Analysis

Abstract: This study investigates how students' views toward undocumented immigrants' access to public education change during college. A multilevel analysis among a national sample of 12,388 undergraduates, drawn from the Cooperative Institutional Research Program's (CIRP) Freshman Survey and College Senior Survey, revealed that significant predictors of senior-year views include various student characteristics and predispositions, political contexts, college experiences, and institutional contexts. Given the often-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Individual predisposition and views are also significant predictors of immigration attitudes, such as political orientation (Chandler andTsai 2001, Fennelly andFederico 2008;Scheve and Slaughter 2001), meritocratic ideologies (Parks-Yancy et al 2009), and economic concerns (Fennelly and Federico 2008;Scheve and Slaughter 2001). Individual experiences including cross-racial interactions have been shown to impact attitudes toward immigrant educational access (Herrera et al, 2013). Beyond the individual-level factors and toward understanding the multiple layers of contexts, emerging research points to three important contextual considerations-demographic, economic, and political.…”
Section: Prior Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Individual predisposition and views are also significant predictors of immigration attitudes, such as political orientation (Chandler andTsai 2001, Fennelly andFederico 2008;Scheve and Slaughter 2001), meritocratic ideologies (Parks-Yancy et al 2009), and economic concerns (Fennelly and Federico 2008;Scheve and Slaughter 2001). Individual experiences including cross-racial interactions have been shown to impact attitudes toward immigrant educational access (Herrera et al, 2013). Beyond the individual-level factors and toward understanding the multiple layers of contexts, emerging research points to three important contextual considerations-demographic, economic, and political.…”
Section: Prior Literaturementioning
confidence: 99%
“…as individual economic concerns have been shown to affect immigration attitudes (Fennelly and Federico 2008;Scheve and Slaughter 2001). Whether the student was a business major is also accounted for in the model as business majors have been shown to have more restrictive attitudes toward undocumented immigrant access to public education (Herrera et al 2013). Potential intergroup contact in college is measured by two CIRP constructs: positive cross-racial interactions and negative cross-racial interactions.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the second theme focuses on how microsystems around immigrants can lack resources or, due to being immigrants, students are unable to access necessary resources. For example, undocumented students' lack of financial resources for college ties to U.S. public policy and students' inability to qualify for federal financial aid (Flores, 2009;Flores & Horn, 2010;Herrera et al, 2013;Nienhusser, 2014). Each of these themes connects to scholars focusing on low-income, first generation to college, and/or undocumented immigrant populations within their studies, in which broader social stratification and structural inequalities in the U.S. can negatively impact the educational experiences of these students.…”
Section: Negative Depictionsmentioning
confidence: 99%
“…Immigrant students' engagement in various forms of activism on campuses yielded two different outcomes in connection with peer relationships (Deangelo et al, 2016). In one of the few articles focused on peers, Herrera et al (2013) found that undocumented immigrant students face prejudice from their U.S. citizen peers on campus due to their immigration status. In contrast, Nuñez (2009) found that Latino students who are actively engaged in campus life have a higher sense of exclusion because they develop a sense of consciousness that raises their awareness about racial issues that exist on campus and in society at large.…”
Section: Microsystemmentioning
confidence: 99%